Plant Growth-Promoting Ability of Mycorrhizal Fusarium Strain KB-3 Enhanced by Its IAA Producing Endohyphal Bacterium, Klebsiella aerogenes - Cheng, Sheng; Jiang, Jian-Wei; Tan, Li-Tao; Deng, Jian-Xin; Liang, Peng-Yu; Su, Hang; Sun, Zheng-Xiang; Zhou, Yi (Frontiers in Microbiology, 2022)
Fusarium oxysporum KB-3 had been reported as a mycorrhizal fungus of Bletilla striata, which can promote the seed germination and vegetative growth. Endohyphal bacteria were demonstrated in the hyphae of the KB-3 by 16S rDNA PCR amplification and SYTO-9 fluorescent nucleic acid staining. A strain, Klebsiella aerogenes KE-1 was isolated and identified based on multilocus sequence analysis. The endohyphal bacterium was successfully removed from the wild strain KB-3 (KB-3-), and GFP-labeled KE-1 was also transferred to the cured strain KB-3- (KB-3+). The production of indole-3-acetic acid (IAA) in the culturing broths of strains of KE-1, KB-3, KB-3- and KB-3+ was examined by HPLC. Their IAA productions were estimated using Salkowski colorimetric technique. The highest concentrations of IAA were 76.9 (at 48 h after inoculation), 31.4, 9.6 and 19.4 μg/mL (at 60 h after inoculation), respectively. Similarly, the three fungal cultural broth exhibited correlated plant promoting abilities on the tomato root and stem growth. The results indicated that the ability of mycorrhizal Fusarium strain KB-3 to promote plant growth was enhanced because its endohyphal bacterium, Klebsiella aerogenes KE-1 produced a certain amount of IAA.